Enriched CD161high CCR6+γδt cells in the cerebrospinal fluid of patients with multiple sclerosis - Schirmer, Lucas; Rothhammer, Veit; Hemmer, Bernhard; Korn, Thomas (JAMA Neurology, 2013)
Objective: To investigate the expression of CD161 (KLRB1) andCCR6on human γδTcells in blood and cerebrospinal fluid (CSF) of patients with a clinically isolated syndrome (CIS) and multiple sclerosis (MS) in relapse. Design: Flow cytometry analysis of CD161 and CCR6 expression and intracellular cytokine staining for interleukin 17 and interferon-γ on humanγβT cells in blood and CSF samples. Setting: Department of Neurology, Klinikum rechts der Isar, Technische Universität München, a tertiary referral center. Patients: Twenty-six patients with CIS/MS in active relapse, 10 patients with other autoimmune disorders, 12 patients with neuroinfectious diseases, and 15 patients with noninflammatory neurological diseases. Main Outcome Measures: Frequencies of CD161high and CCR6+γδT cells in blood and CSF samples of patients with CIS/MS in relapse and control patients. Results:γδT cells were increased in both blood and CSF of patients with CIS/MS in relapse as compared with controls with noninflammatory disease. The fraction of CD161high CCR6+γδT cells was significantly higher in the CSF of patients with CIS/MS in relapse than of those with systemic autoimmune disorders or controls with noninflammatory disease. The CD161high CCR6+ doublepositive γδT-cell population was further enriched in the CSF in relation to blood in patients with CIS/MS in relapse but not in patients with infectious disease or the other control groups. The CD161high CCR6+γδT-cell population was characterized by its capacity to produce interleukin 17. Conclusion: Interleukin 17-producing CD161high CCR6+ γδT cells might contribute to the compartmentalized inflammatory process in the central nervous system of patients with MS. © 2013 American Medical Association. All rights reserved.
CRIS-Team Scopus Importer:2020-09-22